[Hvalfjord Whaling Station] - Streng, Evelyn Fiedler (1975)
Photograph of a Hvalfjord Whaling Station. The white structures of a stone platform sits below, covered in red whale parts. A circular structure is sat in the bottom right corner of the photograph. The blue fjord shines in the distance below a flat, green mountain.